2010
DOI: 10.1103/physrevlett.105.231102
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Laguerre-Gauss Mode Generation and Interferometry for Gravitational Wave Detectors

Abstract: We report on the first experimental demonstration of higher-order Laguerre-Gauss (LG(p)(ℓ)) mode generation and interferometry using a method scalable to the requirements of gravitational wave (GW) detection. GW detectors which use higher-order LG(p)(ℓ) modes will be less susceptible to mirror thermal noise, which is expected to limit the sensitivity of all currently planned terrestrial detectors. We used a diffractive optic and a mode-cleaner cavity to convert a fundamental LG(0)(0) Gaussian beam into an LG(3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 25 publications
1
62
0
Order By: Relevance
“…The quality of the modes in various points has been estimated by using an adimensional intensity overlap integral γ (already used in [15,16]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the modes in various points has been estimated by using an adimensional intensity overlap integral γ (already used in [15,16]…”
Section: Methodsmentioning
confidence: 99%
“…Up to now, two table-top experiments have demonstrated the generation of a high purity LG 33 mode for GW detection using a diffractive element, either a liquidcrystal-on-silicon spatial-light modulator [14] or a fusedsilica plate [15], in combination with a linear mode-cleaner cavity. Two further experiments have investigated this technique at scales closer to a real gravitational wave detector by increasing either the laser power or the length of the optical system: the former [16] was focused on the LG 33 high-power generation by a diffractive phase plate, while the goal of the latter [17] was to inject an LG 33 mode into a suspended 10-m-long Fabry-Pérot cavity in vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…See [44] for a broad discussion. Gauss-Laguerre modes, in particular, received considerable attention, since they may fit standard spherical-mirror cavities [45], although imposing much tighter mode-matching and astigmatism requirements [46].…”
Section: Wide Beamsmentioning
confidence: 99%
“…Due to the practical advantages associated with the use of spherical mirrors, experimental testing of LG 3,3 modes has begun. It has thus far been demonstrated that these modes can be generated with high efficiency and resonated in tabletop cavities with small mirrors [14,15]. An unpleasant property of higher-order LG modes is that each LG p,l mode is 2p + |l| + 1-fold degenerate, the LG 3,3 mode being 10-fold degenerate.…”
Section: Introductionmentioning
confidence: 99%